MSME Tax Policy Reform in Indonesia: Regulatory Analysis, Digitalization, and Improving Taxpayer Compliance. (E-Jurnal Akuntansi, 2026)
This study aims to analyze the development of MSME tax regulations in Indonesia and their implications for taxpayer compliance. The approach used is qualitative descriptive through a literature study utilizing secondary data from government regulations, scientific articles, and official documents of the Directorate General of Taxes. The analysis results indicate that the implementation of a final Income Tax rate of 0.5% and a tax exemption policy up to a certain turnover limit can improve MSME administrative compliance. Digitization through the CoreTax system also contributes to simplifying the reporting process and improving data accuracy. However, the effectiveness of the policy is still affected by low tax literacy, limited bookkeeping, and unequal access to technology. Thus, the success of MSME tax policies is determined not only by regulations, but also by taxpayers' readiness and understanding in implementing them.
Keywords: MSME Taxation; Taxpayer Compliance; Tax Reform; Tax Digitalization; CoreTax